PEMETAAN TATA BATAS SECARA PARTISIPATIF SETELAH PEMEKARAN DENGAN APLIKASI SISTEM INFORMASI GEOGRAFIS DI KELURAHAN BUGIS KECAMATAN SAMARINDA KOTA - Rini, Djumansi Derita, dan Sri Endayani (Universitas 17 Agustus 1945 Samarinda, 2015)
The background of this research is the existence of Bugis urban village, Samarinda Kota sub district, which is formed in an expansion of Samarinda Kota sub-district on 28th December 2010; the administration map is needed as the reference of Bugis urban village development in the future. Green area space in Bugis urban village is very useful to the aspect of its beauty, shelter, and to decrease the disadvantage of air pollution. The research purpose is to provide participatory boundary mapping (including size of urban village area and its green area) in Bugis urban village after the expansion. The result of the research showed that the area size of Bugis urban village is 69,2 Ha. Meanwhile the green space area is 0.51 Ha. If a village does not provide a boundary mapping and an exact size boundary, it definitely influences the urban planning and regional expansion of the urban village. The existence of green area space need an attention, beside it was useful for the view of village, it is also good influence to reduce solar radiation received and polluted air radiation.